A review of methodologies for research uptake in eco-health projects conducted in rural communities in Sub-Saharan Africa - Tafadzwa Mindu; Moses John Chimbari; Resign Gunda (Communicare)
This review analyses research uptake methods which have been used by researchers in sub- Saharan Africa to determine which methods are effective for communities. The key area of the study is research uptake methods applicable at rural community level. The study analyses how effective these methods are in getting research findings adopted by the community, stirring behaviour change and raising awareness about a problem. The review makes recommendations for research projects that seek to conduct research uptake in the rural areas of sub-Saharan Africa. A systematic search for articles was done using Medline, PubMed and Google Scholar. Articles on the uptake of eco-health research findings at a community level were screened and analysed using narrative synthesis. Results showed that strategies involving media, educational materials and interpersonal communication with the communities worked most effectively. Some examples of these were use of radio programmes, film productions, community theatre, field workers, community meetings, educational programmes, peer education and point of care displays. The study concluded that to enhance research uptake in communities, innovative methods which capture the context of the communities involved need to be used. Selected strategies should use the eco-health approach, engage the community and incorporate indigenous knowledge systems.